Temperature-dependent spatial and temporal trends in archaeal lipid distributions - Siqi Zhao; Rui Bao; Long Zhou; Mingzhi Liu; Xiang Sun; Zhen Gao; Yang Zhou; Nan Wang; Yipeng Wang; Junhui Chen; Lei Xing; Chuanlun Zhang (Communications Earth & Environment)
Abstract Isoprenoid glycerol dialkyl glycerol tetraethers are key archaeal lipids widely applied in biogeochemistry. Compounds with zero cyclopentane rings and those with four cyclopentane and one cyclohexane ring dominate in marine sediments and are crucial for investigating archaeal evolution and adaptation. However, the mechanisms regulating their distribution patterns remain unclear. Here we use molecular dynamics simulations to examine their structural properties under increasing temperatures and find that temperature-dependent behaviors govern their global spatial distributions. Consistent distribution patterns across different geological epochs, revealed by thousands of geochemical records, suggest that Earth’s temperature may have constrained long-term temporal trends of archaeal lipids. Reinforcement learning results further show that average atmospheric carbon dioxide levels since the Late Jurassic are closely associated with these two archaeal lipid distribution patterns, enabling predictions for more ancient sedimentary records, which can benefit for understanding the long-term adaptation strategy for the evolutionary and ecological significance of archaea.